The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/jaha.115.002930
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Obstructive Sleep Apnea in Young and Middle‐Aged Adults: Effects of Positive Airway Pressure and Compliance on Arterial Stiffness, Endothelial Function, and Cardiac Hemodynamics

Abstract: BackgroundThe cardiovascular effects of positive airway pressure (PAP) therapy in obstructive sleep apnea (OSA) patients are not clear because of confounding by comorbid conditions.Methods and ResultsProspective interventional study of PAP therapy and withdrawal. Apnea Hypopnea Index (AHI; events/hour of sleep) was determined from polysomnography. Central aortic blood pressures (BPs), Aortic Augmentation Index (AAIx), and central (PWV c‐f) and peripheral pulse wave (PWV c‐r) velocities were determined by appla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In severely obese patients, CPAP treatment improved but did not normalize pulse wave analysis [36,37] . Other positive short-term effects of CPAP on pulse wave analysis were recently reported by Korcarz et al [38] in a younger and less obese population compared to our patients. In our cohort, patients with events during follow-up showed a trend for higher PWV at diagnosis, although the difference did not reach significance, probably owing to an insufficient sample size.…”
Section: Discussionsupporting
confidence: 84%
“…In severely obese patients, CPAP treatment improved but did not normalize pulse wave analysis [36,37] . Other positive short-term effects of CPAP on pulse wave analysis were recently reported by Korcarz et al [38] in a younger and less obese population compared to our patients. In our cohort, patients with events during follow-up showed a trend for higher PWV at diagnosis, although the difference did not reach significance, probably owing to an insufficient sample size.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, an improvement in vascular stiffness evaluated by pulse wave analysis early in the morning after CPAP therapy has been described, when compared with the same measurements in the afternoon (63). Another study concluded that CPAP improves vascular function even after short-term treatment (64), but also that there is a rapid reversal following CPAP withdrawal (65).…”
Section: Vascular Functionmentioning
confidence: 95%
“…elevated diastolic blood pressure and heart rate) can begin to return within 48–72 h (Kohler et al., ; Turnbull et al., ). Moreover, blood pressure and heart rate continue to increase during 1–2 weeks of CPAP withdrawal (Kohler et al., ; Korcarz, Benca, Barnet, & Stein, ). For patients in the oxygen group, their OSA was not treated (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Air: OSA patients randomized to receive no OSA treatment for two weeks (n = 26). 2011; Korcarz, Benca, Barnet, & Stein, 2016). For patients in the oxygen group, their OSA was not treated (i.e.…”
Section: Post-cpap/follow-up Visitmentioning
confidence: 99%